ANALISIS INTEGRATIF PRINSIP DAN PENDEKATAN PENGEMBANGAN KURIKULUM DALAM REFORMASI PENDIDIKAN NASIONAL - Ziyanah Walidah; Amelia Veviani; Sri Rahmawati; Muhammad Zid; Wini Mustikarani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Merdeka Curriculum represents a major educational reform in Indonesia designed to enhance learning quality through curriculum flexibility, authentic assessment, and the strengthening of the Pancasila Student Profile. This study aims to analyze the underlying principles and approaches in the development of the Merdeka Curriculum as well as the key challenges encountered during its implementation in schools. Employing a literature review method, this research synthesizes policy documents, scholarly articles, and relevant theoretical sources through thematic analysis. The findings indicate that the Merdeka Curriculum offers a more adaptive and learner-oriented framework that aligns with the demands of the 21st century and contemporary global developments. The curriculum provides greater autonomy for teachers and schools, encourages project-based learning, and places a strong emphasis on character development. However, the results also reveal several persistent obstacles, including limited teacher readiness to act as curriculum designers, disparities in technological and digital infrastructure across regions, and inconsistent application of authentic assessment practices. These challenges hinder the full realization of learning transformation as intended by the curriculum. Therefore, future educational reform efforts must prioritize continuous teacher professional development, equitable distribution of educational resources, and the cultivation of an innovative school culture. Strengthening these aspects is essential to ensure that the Merdeka Curriculum can be implemented effectively and that the Pancasila Student Profile can be achieved consistently across diverse educational settings in Indonesia.